Culturally competent research : using ethnography as a meta-framework - Lee, Mo Yee.; Zaharlick, Amy. (New York : Oxford University Press, 2013)
This book provides a practical guide for social work researchers, doctoral students, and professionals who are interested in conducting culturally competent research with diverse populations and groups. 'Culturally Competent Research' adopts ethnography as a meta-framework for conducting culturally competent research. Since its inception as an academic discipline, anthropology has developed theories, concepts, methods, and a significant body of substantive studies for the purposes of guiding cultural research, describing cultural groups and processes, and providing data needed for cross-cultural research and theory-building.
Series from CIP print record.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Jan. 7, 2013).
Keywords: Social service -- Research; Ethnology -- Research